Proses Penetapan Wali Nikah oleh Penghulu terhadap Anak Perempuan yang Dilahirkan Akibat Kehamilan di Luar Perkawinan - Laili, Afrohatul; Nu'man, Moh.; Slamet; Nisa, Irma Naza ‘Aina; Fitria, Lailatul (Comprehensive Journal of Islamic Studies, 2025)
This research examines the process of determining the marriage guardian by the marriage registrar for daughters born from out-of-wedlock pregnancies. Marriage in Islam is a sacred covenant that is clearly regulated, with the guardian being one of the essential pillars that determines the validity of the marriage contract. However, cases of out-of-wedlock pregnancies also referred to as "pregnant marriages" in the Compilation of Islamic Law (KHI) present complex challenges in determining the appropriate marriage guardian for daughters born under such circumstances. Article 99 of the KHI defines a legitimate child as one born within or as a result of a legal marriage. This study employs a library research method (literature review), gathering data from various sources such as books, academic journals, and legal documents to explore relevant theories. The role of the is crucial in determining the guardian for children born from out-of-wedlock pregnancies, taking into account Islamic law, the KHI, and applicable regulations. Penghulus often encounter sensitive situations in which they must compare the date of the parents' marriage with the child's birth date to establish the child's legal lineage. Although different KUA offices may adopt varying approaches ranging from appointing a court-assigned guardian to recognizing the biological father as the lineage guardian based on their interpretation of the KHI all penghulus share a common mission: to uphold maqashid as-syari’ah (the objectives of Islamic law) and to protect the rights and lineage of the child. This careful process in determining the guardian also aims to safeguard the psychological well-being of the prospective bride.